Evaluation of single-dose hypnotic treatment before elective operation. Issue 6244 (27th September 1980) - Keighley, M R; Gannon, M; Warlow, J; Jenkins, C R; Gammon, R J
Abstract : A prospective randomised double-blind controlled trial was carried out to evaluate the place of a single dose of triazolam, flurazepam, and placebo on the evening before an elective operation in 96 patients. Features of sleep were recorded by patients and nurses on questionnaires. Onset of sleep was delayed and duration of sleep reduced in two-thirds of patients allocated placebo compared with their normal sleep pattern. Two-thirds of these patients also complained of waking more than twice during the night. Both hypnotics significantly improved the duration and time of onset of sleep and reduced the frequency of wakening when compared with the placebo. Patients who took triazolam, however, fell asleep faster and woke less often than those who took flurazepam. Furthermore, triazolam appeared to have advantages over flurazepam before surgery. Thus giving a single dose of a hypnotic on the night before an elective operation improves the patient's sleep, and greater benefit was derived from triazolam than flurazepam.